2019
DOI: 10.1016/j.ccell.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Editing of Cell-Cycle Regulatory and Tumor Suppressor RNA Promotes Malignant Progenitor Propagation

Abstract: Adenosine deaminase associated with RNA1 (ADAR1) deregulation contributes to therapeutic resistance in many malignancies. Here we show that ADAR1-induced hyper-editing in normal human hematopoietic progenitors impairs miR-26a maturation, which represses CDKN1A expression indirectly via EZH2, thereby accelerating cell-cycle transit. However, in blast crisis chronic myeloid leukemia progenitors, loss of EZH2 expression and increased CDKN1A oppose cell-cycle transit. Moreover, A-to-I editing of both the MDM2 regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 72 publications
(120 reference statements)
1
87
0
Order By: Relevance
“…When comparing the A-to-I editing status, scientists revealed the elevated frequency of 3'UTR editing events in malignant progenitor cells. Interestingly, the majority of A-to-I events occurred in the 3'UTR of MDM2 RNA transcripts [52]. As an E3 ubiquitin ligase, MDM2 directly associates with and subsequently inactivates the transactivation domain of tumor suppressor p53.…”
Section: A-to-i Modification and Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the A-to-I editing status, scientists revealed the elevated frequency of 3'UTR editing events in malignant progenitor cells. Interestingly, the majority of A-to-I events occurred in the 3'UTR of MDM2 RNA transcripts [52]. As an E3 ubiquitin ligase, MDM2 directly associates with and subsequently inactivates the transactivation domain of tumor suppressor p53.…”
Section: A-to-i Modification and Cancer Stem Cellsmentioning
confidence: 99%
“…When the A-to-I editing occurred in the 3'UTR of MDM2 transcripts, miR-155 no longer bound to the edited 3'UTR ( Fig. 1b), leading to the stabilization of MDM2 and inactivation of p53 [52].…”
Section: A-to-i Modification and Cancer Stem Cellsmentioning
confidence: 99%
“…We applied methods used in our previous studies to detect editing at REDIportal sites in the tumor samples. We filtered out editing sites found in dbSNP (version 147) and COSMIC (version 81), except for reported cancerrelated editing sites 8,13,19,[85][86][87][88] , since editing sites have been shown to be mistakenly recorded as SNPs 89,90 . Within each sample, we also filtered out editing events that overlapped with sample-specific somatic mutations and copy number variants.…”
Section: Quantification and Comparison Of Rna Editing Levelsmentioning
confidence: 99%
“…The first evidence that RNA editing plays an important role in LSC function and maintenance was the discovery that the interferon-inducible isoform of ADAR1, ADAR1p150, is highly upregulated in CML LSCs [7]. Additional studies revealed that ADAR1p150 behaves as a self-renewal factor in LSCs through multiple molecular mechanisms, which include inducing GSK3β missplicing, altering miRNA biogenesis, and introducing 3′ UTR editing to evade miRNA targeting [1,8]. We recently reported that ADAR1 has diverse roles in normal HSC and LSC maintenance [8].…”
Section: A-to-i Rna Editing In Leukemia Stem Cells -Set Adar1 On Thementioning
confidence: 99%
“…Additional studies revealed that ADAR1p150 behaves as a self-renewal factor in LSCs through multiple molecular mechanisms, which include inducing GSK3β missplicing, altering miRNA biogenesis, and introducing 3′ UTR editing to evade miRNA targeting [1,8]. We recently reported that ADAR1 has diverse roles in normal HSC and LSC maintenance [8]. We examined the edited miRNome of 1008 miRNAs and found that in normal Hematopoietic stem cell (HSC), ADAR1-mediated RNA editing accelerates cell cycle transit by impairing miR-26a biogenesis and represses CDKN1A expression indirectly via EZH2 methyltransferase.…”
Section: A-to-i Rna Editing In Leukemia Stem Cells -Set Adar1 On Thementioning
confidence: 99%